OPTIMIZATION OF SURFACE ROUGHNESS IN TURNING S45C CARBON STEEL MATERIAL USING THE TAGUCHI METHOD - Haryanto, Muhammad Fahrudin; Khaerudin, Deni S (Universitas Muhammadiyah Jakarta, 2020)
The value of minimal surface roughness is the performance to be achieved in the Takisawa TSL-800 lathe. Therefore, it is necessary to adjust the variables of the Takisawa TSL-800 lathe process precisely in order to obtain a minimal surface roughness response. Determining the proper settings of the Takisawa TSL-800 lathe process variables will result in the expected surface roughness of the workpiece. The variables of the machining process that are varied are spindle speed, feed rate and depth of cut. The experimental design was determined based on the Taguchi method and was in the form of an Orthogonal L9 matrix (33).